Gerakan Bersih Pantai dan Sosialisasi 3r (Reduce, Reuse, Recycle) di Pantai Batu Mejan - Budiman, Diky; Mulia, Victor Bangun; Prakoso, Ganang Aditiyo (LPPM Universitas Bumigora, 2025)
Bali has a global beach destination, this makes local and foreign tourists visit Bali beaches every day, including the Batu Mejan beach area, Canggu which is the prima donna. The high number of tourist visits makes the waste problem a growing issue. The method used in this service is a participatory rural appraisal approach, namely increasing and empowering community participation in activities. Based on the community service activities carried out, participants increasingly understand that waste is a problem that can be overcome by the 3R method (Reduce, Reuse, Recycle), besides that waste cleanup activities are real activities in protecting the beach from the dangers of waste, which can disturb or damage the ecosystem in the beach environment.